The Effectiveness of Lavender Aromatherapy on Anxiety Levels in Pregnant Women Facing Childbirth - Sri Rahayu; Anik Sri Purwanti (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Anxiety during pregnancy, particularly near the time of delivery, is a common issue that may adversely affect both maternal and fetal health. Elevated anxiety levels are associated with increased pain perception, prolonged labor, and a higher likelihood of complications. Non-pharmacological approaches, such as aromatherapy, are increasingly utilized due to their safety, simplicity, and effectiveness. Lavender aromatherapy is especially recognized for its calming effects and its ability to enhance emotional well-being. Previous research has indicated that lavender scent exposure can reduce both physiological and psychological indicators of anxiety, including among pregnant women. However, evidence from Indonesian primary healthcare settings remains limited. This study aimed to evaluate the effectiveness of lavender aromatherapy in reducing anxiety levels among pregnant women approaching childbirth. An analytical observational design with a pretest-posttest approach was applied to 30 participants selected through purposive sampling. Anxiety levels were assessed using a validated questionnaire before and after inhalation of lavender aromatherapy administered under standardized conditions. Data were analyzed using the Wilcoxon signed-rank test.The findings revealed a significant reduction in anxiety levels after the intervention (p < 0.05), with all participants experiencing improvement and no adverse effects reported. In conclusion, lavender aromatherapy is an effective complementary intervention to reduce anxiety and support maternal readiness for labor.